Eating the IT elephant : moving from greenfield development to brownfield - Hopkins, Richard (IBM Press/Pearson plc, 2008)
A Practical, Start-to-Finish Approach to Managing, Evolving, and Transforming Legacy IT Systems For every IT executive, manager, architect, program leader, project leader, and lead analyst "Richard and Kevin introduce us to a reality that's often neglected in our industry: the problem of evolving legacy systems, a domain they call 'Brownfield development.' The authors identify the root of the problem as that of complexity, and offer an approach that focuses on the fundamentals of abstraction and efficient communication to nibble at this problem of transformation bit by bit. As the old saying goes, the way you eat the elephant is one bite at a time. Richard and Kevin bring us to the table with knife and fork and other tools, and show us a way to devour this elephant in the room." Grady Booch, IBM Fellow, co-creator of UML "Most organizations in the 21st century have an existing, complex systems landscape. It is time that the IT industry face up to the reality of the situation and the need for new development methods and tools that address it. This book describes a new approach to the development of future systems: a structured approach that recognizes the challenges of 'Brownfield' development, is based on engineering principles, and is supported by appropriate tooling." Chris Winter, CEng CITP FBCS FIET, IBM Fellow, Member of the IBM Academy of Technology Most conventional approaches to IT development assume that you're building entirely new systems. Today, "Greenfield" development is a rarity. Nearly every project exists in the context of existing, complex system landscapes--often poorly documented and poorly understood. Now, two of IBM's most experienced senior architects offer a new approach that is fully optimized for the unique realities of "Brownfield" development. Richard Hopkins and Kevin Jenkins explain why accumulated business and IT complexity is the root cause of large-scale project failure and show how to overcome that complexity "one bite of the elephant at a time." You'll learn how to manage every phase of the Brownfield project, leveraging breakthrough collaboration, communication, and visualization tools--including Web 2.0, semantic software engineering, model-driven development and architecture, and even virtual worlds. This book will help you reengineer new flexibility and agility into your IT environment ... integrate more effectively with partners ... prepare for emerging business challenges ... improve system reuse and value ... reduce ...